Raumordnung, Landes- und Regionalplanung: AusgewÄhlte Ergebnisse der Forschungstätigkeit der Akademie für Raumforschung und Landesplanung - Ritter, Ernst-Hasso; Scholich, Dietmar (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
Questions of comprehensive spatial planning at the various levels at which it is undertaken — in contrast to research questions, which tend largely to be concept-based — show a particularly strong orientation to the players active at the various levels of planning. The fields of action within spatial planning and their spatial impacts quite naturally pervade all fields of research. Consequently, these questions clearly have to be seen as displaying an overarching character. The special quality of this relationship is found in the evaluative reflection of spatial research which is carried out through the action fields of spatial planning practice. This article provides an application-based insight into the activities of the ARL workshop on this field of research and into the research findings which have so far been forthcoming.